Fear of failure and academic procrastination among university students: The role of achievement expectancy and year of study - Eunice Wan-Yi Tan; Kususanto Ditto Prihadi (Institute of Advanced Engineering and Science, 2022)
This current study aimed to investigate whether expectancy-value model of achievement choice mediates the relationship between fear of failure (FOF) and academic procrastination (AP) among undergraduate students of Psychology Department at a private university in Malaysia. Based on the Krejcie-Morgan Table and G*Power, 102 undergraduate students (aged 18-24) who enrolled in core subjects were recruited to represent the population via snowball sampling method. PROCESS macro for SPSS was utilized to perform the Bootstrap analysis with 5,000 sampling at 95% confidence interval to test the mediation hypothesis. Results showed a significant positive total effect of FOF on AP and significant negative direct effect of expectancy-value model on academic procrastination, supporting the hypothesis for path c and path b. However, no significant direct effect was found between FOF and expectancy-value model (path a). Mediation did not occur, therefore FOF is still considered a robust and significant predictor of AP among the population of psychology students in the aforementioned university. Furthermore, our results suggested that the aforementioned link did not significantly occur among the first-year students.